LOSS AND GAIN IN TRANSLATION OF BALINESE FOLKLORE ENTITLED “I SIAP BADENG” INTO “THE BLACK HEN” - Agustawan, Dewa Made (IKIP SARASWATI TABANAN, 2025)
This paper explores the concepts of loss and gain in Balinese Folklore. The aim of this research is to analyzed Balinese Folklore entitled “I Siap Badeng” which has been translated into “The Black Hen”. The data was taken from The Book of Balinese Folklore. The data was analyzed descriptively. In analyzing the loss and gain, the research used the theory proposed by Larson (1998), the second is analyzed the conception loss and gain from Bassnet (1991). Based on the analysis that have been done, it can be concluded that gain was more often found in this translation rather than lose. As the example, the researcher got in SL: “Nyanan di pulesne sauh tendas panakne” TL: “Later when they were sleeping I’ll just grab her chicks”. This translation creates a new meaning in TL. So, this phenomenon can move the real meaning of the story in order to save the culture